Analisis Kepuasan Kerja Tenaga Kesehatan di RS. Pertamina Bintang Amin - Dewi Asnida; Samino Samino; Riyanti Riyanti (Universitas Malahayati, 2026)
ABSTRACT Job satisfaction is the way an individual feels his job. Attitudes are closely related to individual work which includes factors such as salary, supervision, situation, opportunities for advancement, awards, abilities, and fair job ratings from the company. The aim is to determine the job satisfaction of health workers at Pertamina Bintang Amin Hospital. This type of quantitative research with a cross sectional approach. The research population is all permanent employees of hospital health workers Pertamina Bintang Amin consisting of nurses, midwives and other medical personnel as many as 148 respondents. Samples that meet the requirements in this study are 148 respondents. The research instrument is a questionnaire. Data analysis using smartPLS SEM (Partial Least Square – Structural Equation Modeling) Software. The results of this study obtained Path Coefficient Compensation 0.149 t statistic 1.767, Path Coefficient promotion opportunities 0.392 t statistics 4.449, Supervision Path Coefficient 0.450 t statistics 5.715 on job satisfaction. Work compensation influences through motivation because the influence value is 0.3876, Promotional opportunities influence through motivation because the influence value is 0.3956, Supervision influences through motivation is received with an influence value of 0.3876 on the satisfaction of health workers at Pertamina Bintang Amin Hospital. Suggestions from this study are expected to pay attention to and increase the level of job satisfaction, and aspects that can affect the level of job satisfaction Keywords: Satisfaction, Health Workers, Hospital Pertamina Bintang Amin. ABSTRAK Kepuasan kerja adalah cara seorang individu merasakan pekerjaannya. Kepuasan kerja sebagai hasil dari berbagai sikap yang ditunjukkan oleh seorang karyawan, Sikap berkaitan erat dengan pekerjaan individu yang meliputi faktor-faktor seperti gaji, supervisi, situasi, peluang untuk maju, penghargaan, kemampuan, dan penilaian pekerjaan yang adil dari perusahaan. Tujuan untuk menganalisis kepuasan kerja pada tenaga kesehatan di RS Pertamina Bintang Amin. Jenis penelitian kuantitatif dengan pendekatan cross sectional. Populasi penelitian semua pegawai tetap tenaga kesehatan RS. Pertamina Bintang Amin yang terdiri atas perawat, bidan, dan tenaga medis lainnya sebanyak 148 responden. Sampel yang memenuhi syarat dalam penelitian 148 responden. Instrumen penelitian adalah kuesioner. Analisa data menggunakan Software smartPLS SEM (Partial Least Square – Structural Equation Modeling). Hasil dari penelitian ini didapatkan Kompensasi Path Coefficient 0,149 t statistik 1,767, Kesempatan promosi Path Coefficient 0,392 t statistik 4,449, Supervisi Path Coefficient 0,450 t statistik 5,715 terhadap kepuasan kerja, Kompensasi kerja berpengaruh melalui motivasi karena nilai pengaruh 0,3876, Kesempatan promosi berpengaruh melalui motivasi karena nilai pengaruh 0,3956, Supervisi berpengaruh melalui motivasi diterima dengan nilai pengaruh 0,3876 terhadap kepuasan tenaga kesehatan di RS Pertamina Bintang Amin. Saran dari penelitian ini diharapkan dapat memperhatikan dan meningkatkan tingkat kepuasan kerja, dan aspek-aspek yang dapat mempengaruhi tingkat kepuasan kerja Kata Kunci: Kepuasan, Tenaga Kesehatan, RS. Pertamina Bintang Amin